Air electrode for air secondary battery, and method for manufacturing air electrode

JP2025082006APending Publication Date: 2025-05-28FDK CORP

Patent Information

Application Number
JP2023195176
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-11-16
Publication Date
2025-05-28

Smart Images

  • Figure 2025082006000001_ABST
    Figure 2025082006000001_ABST
Patent Text Reader

Abstract

To provide an air electrode for an air secondary battery, which is capable of reducing an amount of a catalyst to be used in comparison with conventional ones and which is also excellent in output characteristics and durability, and a method for manufacturing the air electrode.SOLUTION: An air electrode 2 includes a nickel foam 9a, a gas diffusion layer 6 crimped on one side of the nickel foam 9a, and a catalyst layer 8 formed on the other side of the nickel foam 9a. The gas diffusion layer 6 is located in a position, of an air secondary battery 4, facing the atmosphere, and includes a first conductive material having conductivity and a first fluororesin having water repellency. The catalyst layer 8 is located inside the air secondary battery 4, and includes a catalyst having dual functions of oxygen evolution and oxygen reduction, a second conductive material having conductivity, and a second fluororesin having water repellency.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to an air electrode for an air secondary battery and a method for manufacturing the air electrode. [Background technology]

[0002] In recent years, air batteries, which use atmospheric oxygen as the positive electrode active material, have attracted attention due to their high energy density and ease of miniaturization and lightweight design. Among such air batteries, zinc-air primary batteries have been put to practical use as power sources for hearing aids.

[0003] Additionally, research is being conducted on rechargeable air batteries that use Zn, Fe, Al, Mg, hydrogen storage alloys, etc. as the negative electrode metal, and these air secondary batteries are expected to be new secondary batteries that may have the potential to exceed the energy density of lithium-ion secondary batteries.

[0004] One type of such air secondary battery is known as an air secondary battery that uses an alkaline aqueous solution (hereinafter also referred to as alkaline electrolyte) as the electrolyte (see, for example, Patent Document 1). In air secondary batteries that use alkaline electrolyte like the above-mentioned air secondary battery, the following charge / discharge reactions occur at the positive electrode (hereinafter also referred to as air electrode).

[0005] Charging (oxygen generation reaction): 4OH - →O2+2H2O+4e - (I) Discharge (oxygen reduction reaction): O2 + 2H2O + 4e - →4OH - (II)

[0006] In an air secondary battery, oxygen in the air is reduced during discharge to generate hydroxide ions in the alkaline electrolyte, and during charge, the hydroxide ions in the alkaline electrolyte are oxidized to generate oxygen and water. The oxygen generated during charge passes through pores inside the air electrode and is released into the atmosphere from the part of the air electrode that is open to the atmosphere.

[0007] In air secondary batteries, a catalyst that promotes the above-mentioned charge-discharge reactions is used in the air electrode, which is the positive electrode. This catalyst has the dual functions of oxygen reduction and oxygen generation, and is required to have high activity and durability in the oxygen reduction and oxygen generation reactions. An example of such a catalyst is a bismuth ruthenium composite oxide with a pyrochlore structure.

[0008] The air electrode has a shape in which an air electrode mixture containing the above-mentioned catalyst is held by a core. This air electrode mixture contains the above-mentioned catalyst, a conductive material responsible for electronic conductivity, and a fluororesin as a water repellent, and has a porous structure containing many fine pores into which the alkaline electrolyte and oxygen are taken.

[0009] At the air electrode, a three-phase interface of solid, liquid, and gas is formed by the catalyst, electrolyte, and air (oxygen). During discharge, oxygen is reduced at the three-phase interface to form OH. - The oxygen atoms diffuse into the electrolyte as ions. Therefore, in order to improve the discharge characteristics, it is necessary to form many three-phase interfaces to increase the efficiency of the discharge reaction, and to have air passages that can quickly supply oxygen to the three-phase interfaces.

[0010] In addition, the air electrode is required to be stable even at high potentials and in an oxidizing atmosphere during charging, and is also required to have the properties of being able to suppress catalyst detachment due to oxygen generation during charging and being able to quickly discharge generated oxygen outside the system.

[0011] In order to meet the above-mentioned demands, various studies have been conducted on air electrodes for air secondary batteries.

[0012] For example, Patent Document 2 reports an air electrode using nickel powder as a conductive material. The air secondary battery described in Patent Document 2 has high charge / discharge cycle stability because it uses oxidation-resistant nickel as a conductive material. However, the specific surface area of ​​the conductive material is small, making it impossible to increase the three-phase interface, which poses a problem in that a large amount of catalyst is required to obtain effective output characteristics.

[0013] Furthermore, Patent Document 3 reports an air electrode with a two-layer structure consisting of a gas diffusion layer and a catalyst layer. The air secondary battery described in Patent Document 3 has excellent gas diffusion properties due to the presence of a gas diffusion layer. However, there is a problem in that the adhesion between the gas diffusion layer and the catalyst layer is poor, and the catalyst layer peels off due to the generation of oxygen gas during charging. In particular, when a fluororesin porous membrane or a mixture with a high fluororesin ratio is used to increase the water repellency of the gas diffusion layer, peeling of the catalyst layer becomes more pronounced due to the low surface energy.

[0014] Furthermore, Non-Patent Document 1 reports an air electrode formed by filling nickel foam with a slurry containing a bismuth-ruthenium composite oxide catalyst, graphite, and a fluororesin. The air secondary battery described in Non-Patent Document 1 has a metal foam such as nickel foam that holds the catalyst layer, preventing the catalyst layer from falling off even when oxygen gas is generated during charging, while also ensuring current collection. However, because the electrolyte permeates along the skeleton of the nickel foam, the water repellency of the air electrode is insufficient, posing a problem in output characteristics. [Prior art documents] [Patent documents]

[0015] [Patent Document 1] Japanese Patent Application Laid-Open No. 2006-196329 [Patent Document 2] Japanese Patent Application Publication No. 2020-077469 [Patent Document 3] Japanese Patent Publication No. 2020-013662 [Non-Patent Document 1] Author: Miki Inoue et al., Title: "Air electrode for air secondary batteries with reduced catalyst amount", Proceedings of the 62nd Battery Symposium (2021) Summary of the Invention [Problem to be solved by the invention]

[0016] As described above, in the air electrodes of conventional air secondary batteries, pursuing durability leads to a decrease in output characteristics, and vice versa. Therefore, if one tries to improve output characteristics while maintaining durability, one has no choice but to increase the amount of catalyst.

[0017] However, catalyst materials such as bismuth ruthenium composite oxides often contain expensive noble metals, and increasing the amount of catalyst to improve output characteristics poses a problem of increased manufacturing costs.

[0018] To put air secondary batteries into practical use, it is necessary to reduce manufacturing costs, which requires reducing the amount of catalyst used.

[0019] However, in the case of current air electrodes for air secondary batteries, improving the output characteristics without increasing the amount of catalyst used is likely to result in a problem of reduced durability. Therefore, there is a need to develop an air electrode that has excellent output characteristics and durability while using a reduced amount of catalyst.

[0020] The present invention has been made in light of the above circumstances, and an object of the present invention is to provide an air electrode for an air secondary battery that can reduce the amount of catalyst used compared to conventional methods and that is excellent in output characteristics and durability, and a method for manufacturing the air electrode. [Means for solving the problem]

[0021] In order to achieve the above-mentioned object, according to the present invention, there is provided an air electrode for an air secondary battery used in the positive electrode of an air secondary battery, comprising a metal foam that forms the core of the positive electrode, a gas diffusion layer pressed onto one side of the metal foam, and a catalyst layer formed on the other side of the metal foam, wherein the gas diffusion layer is positioned in a position facing the atmosphere in the air secondary battery and contains a first conductive material that is conductive and a first fluororesin that is water-repellent, and the catalyst layer is positioned inside the air secondary battery and contains a catalyst that has the dual functions of oxygen generation and oxygen reduction, a second conductive material that is conductive, and a second fluororesin that is water-repellent. [Effects of the Invention]

[0022] The air electrode for an air secondary battery according to the present invention is an air electrode for use as a positive electrode of an air secondary battery. The air electrode includes a metal foam core, a gas diffusion layer press-bonded to one side of the metal foam, and a catalyst layer formed on the other side of the metal foam. The gas diffusion layer is positioned in a position facing the atmosphere in the air secondary battery and includes a first conductive material and a first water-repellent fluororesin. The catalyst layer is positioned inside the air secondary battery and includes a catalyst with dual functions of oxygen generation and oxygen reduction, a second conductive material, and a second water-repellent fluororesin. In the air electrode of the present invention, the metal foam core is interposed between the gas diffusion layer and the catalyst layer, ensuring excellent current collection and creating a complex bond between the gas diffusion layer and the catalyst layer. This complex bond increases the number of three-phase interfaces in the catalyst layer and inhibits catalyst layer shedding through an anchoring effect. Furthermore, the gas diffusion layer ensures a diffusion path for oxygen gas to the catalyst layer, allowing oxygen to be rapidly supplied to the three-phase interface of the catalyst layer, improving the efficiency of the discharge reaction. Therefore, excellent output characteristics can be achieved even with a reduced amount of catalyst. Therefore, the present invention provides an air electrode for an air secondary battery that can reduce the amount of catalyst used compared to conventional methods and that also has excellent output characteristics and durability, as well as a method for manufacturing this air electrode. [Brief explanation of the drawings]

[0023] [Figure 1] 1 is a schematic diagram illustrating an air secondary battery including an air electrode according to an embodiment of the present invention. [Figure 2] 1 is a cross-sectional view schematically illustrating an air electrode of Example 1. FIG. [Figure 3] FIG. 2 is a cross-sectional view schematically showing the air electrode of Comparative Example 1. [Figure 4] FIG. 10 is a cross-sectional view schematically showing the air electrode of Comparative Example 2. [Figure 5] 1 is a photograph, substituted for a drawing, showing an SEM / EDS image of the air electrode of Example 1. [Figure 6] 1 is a graph showing a cyclic voltammogram in an oxygen reduction reaction. [Figure 7] 1 is a graph showing a cyclic voltammogram in an oxygen reduction reaction when the current value is converted into a current value per amount of catalyst used. DETAILED DESCRIPTION OF THE INVENTION

[0024] Hereinafter, an air electrode 2 for an air secondary battery according to this embodiment and an air secondary battery (hereinafter also referred to as a battery) 4 including this air electrode 2 will be described with reference to the drawings.

[0025] As shown in the enlarged view in FIG. 1, the air electrode 2 includes a core 9, a gas diffusion layer 6 pressure-bonded to one side of the core 9, and a catalyst layer 8 formed on the other side of the core 9.

[0026] The core 9 is made of a porous material that has excellent gas diffusion properties and the ability to hold the gas diffusion layer 6 and the catalyst layer 8. Known porous materials include perforated metal, expanded metal, and foam metal. Perforated metal is not suitable for the core 9 because its low aperture ratio may hinder gas diffusion. Expanded metal has large pores, which reduces its ability to hold the gas diffusion layer 6 and the catalyst layer 8. Therefore, expanded metal is also not suitable for the core 9. In contrast to perforated metal and expanded metal, foam metal has a small skeleton and small pores, which improves its ability to hold the gas diffusion layer 6 and the catalyst layer 8 (anchor effect). Foam metal also has a large aperture ratio, which improves gas diffusion. Therefore, foam metal is suitable for the core 9. A suitable example of such foam metal is a foam metal made of nickel (nickel foam 9a). Foam metal made of a metal other than nickel can also be used as long as it is stable at the air electrode potential.

[0027] The gas diffusion layer 6 has a porous structure with excellent gas diffusion properties, allowing air to be smoothly introduced into the battery 4 system and released out of the battery 4 system. The gas diffusion layer 6 also has leak-proof properties, preventing the alkaline electrolyte in the battery 4 system from leaking out of the battery 4 system. The structure of this gas diffusion layer 6 is made of a mixture of graphite particles (first conductive material) and fluororesin (first fluororesin). In the gas diffusion layer 6, the gaps between the graphite particles become pores through which air can pass, forming a porous structure as a whole. It is preferable to use high-purity graphite of battery grade for the graphite particles.

[0028] Graphite can be pulverized to obtain graphite particles with a desired average particle size. As the average particle size of the graphite particles decreases, the specific surface area increases, but the crystallinity decreases. As the crystallinity decreases, the oxidation resistance decreases. For this reason, it is preferable to use graphite particles (first graphite particles) with a relatively large average particle size in the gas diffusion layer 6 in order to ensure oxidation resistance and improve gas diffusibility. For example, it is preferable to use graphite particles with an average particle size of 5 μm or more and 20 μm or less in the gas diffusion layer 6.

[0029] In this specification and claims, unless otherwise specified, the average particle size refers to the volume average particle size (MV) measured by a laser diffraction / scattering particle size distribution analyzer.

[0030] On the other hand, the fluororesin (first fluororesin) has water-repellent properties and therefore prevents leakage of the alkaline electrolyte. The amount of the fluororesin (first fluororesin) mixed is preferably 20 wt% or more and 50 wt% or less relative to the graphite particles (first graphite particles). It is preferable to use polytetrafluoroethylene (hereinafter also referred to as PTFE) as the fluororesin (first fluororesin). PTFE not only exhibits high water-repellent properties but also fibrillates and becomes entangled with the surrounding graphite particles, thereby contributing to the strength of the gas diffusion layer 6. Effective methods for promoting the fibrillation of PTFE include increasing the temperature during mixing, using ethanol instead of water as an auxiliary agent during mixing, or using ethanol together with water.

[0031] The catalyst layer 8 contains a catalyst, a conductive material (second conductive material) that provides conductivity to the catalyst layer 8 and supports the catalyst, and a water repellent that provides water repellency to the catalyst layer 8. Furthermore, it is preferable to add manganese dioxide to the catalyst layer 8, which decomposes hydrogen peroxide, which is an intermediate in the discharge reaction.

[0032] The catalyst used has the dual functions of oxygen generation and oxygen reduction. Such a dual-function catalyst contributes to reducing the overvoltage of the battery during both the charging and discharging processes. As such an oxidation-reduction catalyst, for example, a pyrochlore-type bismuth ruthenium composite oxide is preferably used. This bismuth ruthenium composite oxide has the composition formula Bi2Ru2O 7-z (where z satisfies the relationship 0≦z≦1.)

[0033] A carbon material is used for the conductive material (second conductive material). Graphite particles (second graphite particles) are used as this carbon material, and it is preferable to use a high-purity battery-grade product, similar to the graphite particles (first graphite particles) in the gas diffusion layer 6. In the catalyst layer 8, in order to provide as many locations as possible where charge / discharge reactions occur, it is necessary to increase the specific surface area of ​​the graphite particles, which also serve as a catalyst support. In order to increase the specific surface area, it is preferable to use graphite particles with as small an average particle size as possible. Specifically, it is preferable that the average particle size of the graphite particles (second graphite particles) used in the catalyst layer 8 be 3 μm or less.

[0034] As described above, the first graphite particles in the gas diffusion layer 6 are graphite particles with a relatively large average particle size in order to ensure oxidation resistance and improve gas diffusibility, while the second graphite particles in the catalyst layer 8 are graphite particles with a relatively small average particle size in order to increase the specific surface area in order to enhance reactivity. In other words, the first graphite particles in the gas diffusion layer 6 and the second graphite particles in the catalyst layer 8 are required to have different properties, and it is necessary to enhance each of these properties. Therefore, it is preferable that the average particle size of the first graphite particles in the gas diffusion layer 6 is larger than the average particle size of the second graphite particles in the catalyst layer 8.

[0035] A fluororesin (second fluororesin) is used as the water repellent. This fluororesin (second fluororesin) is not particularly limited as long as it is stable against charge / discharge reactions. A preferred fluororesin (second fluororesin) is perfluoroethylene propene copolymer (FEP). Since FEP does not form fibers, it is possible to avoid problems such as the catalyst layer slurry being partially agglomerated due to fiberization of the fluororesin when prepared for forming the catalyst layer, or instability in the amount of coating, as will be described later.

[0036] Next, the air electrode 2 can be manufactured, for example, as follows. First, a sheet-shaped metal foam (nickel foam 9a) made of nickel is prepared as the core 9 (metal foam preparation step). The physical properties of the prepared nickel foam 9a are, for example, a nickel purity of 99.9 wt% or more and an areal density of 280 to 320 g / m 2 , and the porosity is 95% or more.

[0037] Next, a gum-like gas diffusion layer precursor to be used for forming the gas diffusion layer 6 is prepared (gas diffusion layer precursor preparation step).

[0038] In the gas diffusion layer precursor preparation process, graphite particles (first graphite particles) with an average particle size of 5 μm, a dispersion of PTFE (first fluororesin), ethanol, and water are kneaded to form a viscoelastic, gum-like gas diffusion layer precursor. At this time, the mixture ratio of graphite particles to PTFE is 5:3 in terms of solid content weight. The gas diffusion layer precursor obtained as described above is rolled into a sheet.

[0039] Next, a catalyst layer slurry to be used for forming the catalyst layer 8 is prepared (catalyst layer slurry preparation step).

[0040] In the catalyst layer slurry preparation step, first, a pyrochlore-type bismuth-ruthenium composite oxide as a catalyst for the air electrode is produced by a commonly known production method. The obtained bismuth-ruthenium composite oxide is then crushed using a wet bead mill (solvent: water, media: 0.1 mm diameter zirconia beads). Then, a dispersion of graphite particles (second graphite particles) with a particle size of 1 to 2 μm, manganese dioxide, and FEP (second fluororesin) is added to this crushed dispersion and stirred using a planetary mixer to produce catalyst layer slurry. The mixing ratio at this time is, for example, bismuth-ruthenium composite oxide:graphite particles:manganese dioxide:FEP=35:30:15:30 in terms of solids weight.

[0041] Next, the gum-like gas diffusion layer precursor is pressure-bonded to one side of the sheet-like nickel foam 9a (pressure-bonding process). At this time, since the gas diffusion layer precursor is gum-like and viscoelastic, the nickel foam 9a bites into the gas diffusion layer precursor and penetrates into the pores of the nickel foam 9a. A first composite is then obtained in which the gas diffusion layer precursor and the nickel foam 9a are combined. In this first composite, the gas diffusion layer precursor is positioned on one side and the nickel foam 9a is positioned on the other side. On one side of the first composite, the nickel foam 9a is not exposed, and the gas diffusion layer precursor occupies the entire surface. On the other side of the first composite, the skeleton of the nickel foam 9a and the gas diffusion layer precursor present in the pores formed between the skeleton of the nickel foam 9a are exposed.

[0042] Next, the first composite body is subjected to a heat treatment to convert the gas diffusion layer precursor into a gas diffusion layer (gas diffusion layer formation heat treatment step). Specifically, the first composite body is placed in a nitrogen gas atmosphere and maintained at 300°C to 400°C for a predetermined time. This heat treatment evaporates the surfactant and water in the PTFE dispersion. As a result, the gas diffusion layer precursor becomes a gas diffusion layer, and a second composite body is obtained in which the gas diffusion layer 6 and nickel foam 9a are combined.

[0043] Next, the catalyst layer slurry prepared as described above is applied to the other side of the second composite (catalyst layer slurry application step). A predetermined amount of the catalyst layer slurry is applied to the entire other side of the second composite using a bar coater. At this time, the catalyst layer slurry is applied onto the skeletal portion of the nickel foam 9a and the exposed portion of the gas diffusion layer between the skeletal portions of the nickel foam 9a. This results in an intermediate air electrode product in which the gas diffusion layer, nickel foam 9a, and catalyst slurry are combined.

[0044] Next, the intermediate product is subjected to a heat treatment to convert the catalyst layer slurry into a catalyst layer (catalyst layer formation heat treatment step). Specifically, the intermediate product is placed in a nitrogen gas atmosphere and maintained at 300°C to 400°C for a predetermined time. This heat treatment evaporates the surfactant and water in the FEP dispersion. As a result, the catalyst layer slurry becomes the catalyst layer 8, and an air electrode 2 comprising the gas diffusion layer 6, nickel foam 9a, and catalyst layer 8 is obtained.

[0045] In the obtained air electrode 2, the gas diffusion layer 6 is positioned on one side of the nickel foam 9a as a core, and the catalyst layer 8 is positioned on the other side of the nickel foam 9a. In other words, the nickel foam 9a as a core is interposed between the gas diffusion layer 6 and the catalyst layer 8.

[0046] The air electrode 2 is disposed in the air secondary battery 4 so that the gas diffusion layer 6 is positioned on the side in contact with the atmosphere and the catalyst layer 8 is positioned on the side in contact with the alkaline electrolyte. If the alkaline electrolyte inside the battery permeates the gas diffusion layer 6, it will lead to leakage. To prevent leakage, the gas diffusion layer 6 must be given higher water repellency than the catalyst layer 8. Therefore, it is preferable that the proportion of the fluororesin (first fluororesin) contained in the gas diffusion layer 6 be higher than the proportion of the fluororesin (second fluororesin) contained in the catalyst layer 8. Specifically, it is preferable that the content (wt%) of the fluororesin (first fluororesin) contained in the gas diffusion layer 6 be higher than the content (wt%) of the fluororesin (second fluororesin) contained in the catalyst layer 8. Furthermore, it is more preferable to have the content (wt%) of the fluororesin (first fluororesin) contained in the gas diffusion layer 6 be higher than the content (wt%) of the fluororesin (second fluororesin) contained in the catalyst layer 8. Having the content (wt%) of the fluororesin (first fluororesin) contained in the gas diffusion layer 6 higher than the content (wt%) of the fluororesin (second fluororesin) contained in the catalyst layer 8 is thus more preferable, since it facilitates air escape from the catalyst layer 8 to the gas diffusion layer 6 during charging.

[0047] Here, in addition to the method using a gum-like gas diffusion layer precursor, other methods such as coating and printing can also be considered for forming the gas diffusion layer. However, for the following reasons, the method of compressing a gum-like gas diffusion layer precursor employed in this embodiment is superior because it can suppress peeling and reduce the amount of catalyst.

[0048] Before heat treatment, the gas diffusion layer precursor is water-absorbent due to the residual surfactant in the PTFE dispersion. Therefore, when applying the slurry by scraping off excess slurry using a bar coater or a slit, the slurry thickens during application, leading to uneven application. Therefore, heat treatment to make the slurry water-repellent is necessary before application. On the other hand, when applying a predetermined amount of slurry using methods such as screen printing or spray application, the application speed can be increased by leaving the slurry water-absorbent without heat treatment before application. If screen printing or spray application were to be used to fabricate an air electrode with a structure similar to that of this embodiment, possible methods include applying a catalyst layer to the gas diffusion layer and then crimping nickel foam 9a onto it, or crimping nickel foam 9a filled with a catalyst layer onto the gas diffusion layer. However, the former method suffers from the problem of catalyst layer peeling during crimping, while the latter method has limitations in thinning the catalyst layer (reducing the catalyst amount). In contrast, the method of crimping a gum-like gas diffusion layer precursor does not encounter the aforementioned problems and drawbacks associated with application or printing.

[0049] Next, a three-electrode battery 4 that can be used for electrochemical measurements will be described below as an example of an air secondary battery incorporating the air electrode of this embodiment.

[0050] As shown in FIG. 1, the battery 4 includes a working electrode container 10, a reference electrode container 14 connected to the working electrode container 10 via a liquid junction 12, an air electrode 2 and a counter electrode 30 disposed in the working electrode container 10, and a reference electrode 16 disposed in the reference electrode container 14.

[0051] The working electrode container 10 is box-shaped and made of acrylic, and has a sidewall opening 20 formed in part of its sidewall 18. This sidewall opening 20 has a shape similar to that of the air electrode 2 in a plan view, but is slightly smaller than the air electrode 2. The air electrode 2 is disposed so as to cover the sidewall opening 20 from the outside of the sidewall 18. In other words, the sidewall opening 20 is closed by the air electrode 2. The periphery of the air electrode 2 is fixed to the outside of the working electrode container 10 by an acrylic frame member 22. The frame member 22 has an opening 24 in its center that has the same shape as the sidewall opening 20, and is fixed to the sidewall 18 of the working electrode container 10 with screws 26. The gas diffusion layer 6 side of the air electrode 2 is positioned outside the working electrode container 10, and the catalyst layer 8 side is positioned inside the working electrode container 10. That is, the catalytic layer 8 of the air electrode 2 is exposed to the inside of the working electrode container 10, and the gas diffusion layer 6 is open to the atmosphere. A gasket (not shown) is provided where the air electrode 2 and the side wall 18 overlap, and the catalytic layer 8 of the air electrode 2 is in close contact with the side wall 18 around the side wall opening 20, ensuring airtightness.

[0052] An alkaline electrolyte 28 is stored inside the working electrode container 10. As described above, the catalyst layer 8 of the air electrode 2 is exposed to the inside of the working electrode container 10, and therefore the catalyst layer 8 of the air electrode 2 is in contact with the alkaline electrolyte 28.

[0053] In addition, a counter electrode 30 made of a nickel plate having an area significantly larger than that of the air electrode 2 is disposed in the working electrode container 10 at a position facing the air electrode 2. The counter electrode 30 is completely immersed in the alkaline electrolyte 28.

[0054] The air electrode 2 is electrically connected to an air electrode lead 32, and the counter electrode 30 is electrically connected to a counter electrode lead .

[0055] The reference electrode container 14 is a box-shaped container made of acrylic, with a lid 38 fitted into an opening 36 at the top. An alkaline electrolyte 28 is stored inside the reference electrode container 14. A reference electrode 16 is disposed at a predetermined position on the lid 38. The reference electrode 16 is an Hg / HgO electrode, and approximately half of it is immersed in the alkaline electrolyte 28. The reference electrode container 14 is connected to the working electrode container 10 via a liquid junction 12 to eliminate the influence of a liquid junction potential difference. A reference electrode lead 40 is electrically connected to the reference electrode 16.

[0056] As the alkaline electrolyte 28, a general alkaline electrolyte used in alkaline secondary batteries is suitably used, and specifically, an aqueous solution containing at least one of NaOH, KOH, and LiOH as a solute is used.

[0057] In the battery 4, oxygen is generated at the air electrode 2 by charging via the air electrode lead 32 and the counter electrode lead 34, and this oxygen passes through the interior of the air electrode 2 and is released into the atmosphere from the portion of the gas diffusion layer 6 that is open to the atmosphere. On the other hand, during discharge, oxygen in the air taken in from the atmosphere via the gas diffusion layer 6 is reduced, causing a discharge reaction, and a discharge current can be output via the air electrode lead 32 and the counter electrode lead 34.

[0058] Here, the battery 4 of this embodiment is not limited to the above-described three-electrode battery, but may be another air secondary battery having two electrodes, a positive electrode and a negative electrode. Examples of such air secondary batteries include an air secondary battery that includes a container and an electrode group housed in the container together with an alkaline electrolyte, the electrode group including a positive electrode and a negative electrode stacked with a separator interposed therebetween, and the air electrode according to this embodiment is used as the positive electrode. It is also possible to form an air-hydrogen secondary battery that employs a negative electrode containing a hydrogen storage alloy as the negative electrode.

[0059] [Example] 1. Battery manufacturing Example 1 (1) Synthesis of air electrode catalyst 1) Co-precipitation process A predetermined amount of Bi(NO3)3·5H2O and RuCl3·3H2O was prepared and added to distilled water at 75°C so that the Bi(NO3)3·5H2O and RuCl3·3H2O concentrations were equal. The mixture was then stirred to prepare a mixed solution of Bi(NO3)3·5H2O and RuCl3·3H2O. A 2 mol / L NaOH solution was then added to the mixed solution. The bath temperature was set at 75°C, and the mixture was stirred while oxygen was being bubbled through. The resulting solution, containing the precipitate, was then maintained at 85°C to partially evaporate the water, forming a paste. The paste was then transferred to an evaporating dish, heated to 120°C, and held there for 12 hours to dry, yielding a dried paste (precursor).

[0060] 2) Firing process The dried product was placed in a mortar and crushed with a pestle. The mixture was heated to 600°C in an air atmosphere and held for 1 hour to obtain a fired product. The fired product was washed with distilled water at 70°C, filtered under suction, and then dried at 120°C for 3 hours to obtain a pyrochlore-type bismuth ruthenium composite oxide.

[0061] The obtained bismuth ruthenium composite oxide was placed in a mortar and pulverized with a pestle to obtain a bismuth ruthenium composite oxide powder which is an aggregate of particles having a predetermined particle size. When the secondary electron image of this bismuth ruthenium composite oxide powder was observed with a scanning electron microscope, the particle size of the bismuth ruthenium composite oxide was found to be 0.1 μm or less.

[0062] 3) Acid treatment process A nitric acid aqueous solution adjusted to a concentration of 2 mol / L and bismuth ruthenium composite oxide powder were placed in a stirring tank with a stirrer, and stirred for 1 hour while maintaining the temperature of the nitric acid aqueous solution at 25° C. At this time, the amount of the nitric acid aqueous solution was adjusted so that the ratio was 20 mL per 1 g of bismuth ruthenium composite oxide powder.

[0063] After stirring was completed, the bismuth ruthenium composite oxide powder was removed from the nitric acid aqueous solution by suction filtration. The removed bismuth ruthenium composite oxide powder was washed with 1 liter of distilled water heated to 70°C. After washing, the bismuth ruthenium composite oxide powder was dried by being kept in an atmosphere of 120°C for 3 hours.

[0064] In this way, an acid-treated powder of bismuth ruthenium composite oxide (Bi2Ru2O7) was obtained. By carrying out the acid treatment in this manner, it is possible to remove by-products generated in the process of producing the bismuth ruthenium composite oxide.

[0065] 4) Crushing process The bismuth ruthenium composite oxide powder that underwent the acid treatment process aggregated into relatively large lumps, requiring a crushing process. Ion-exchanged water was prepared in an amount such that the solids ratio per weight of the bismuth ruthenium composite oxide powder that underwent the acid treatment process was 10 wt%. A dispersant (ammonium polycarboxylate, manufactured by San Nopco Co., Ltd., SN Dispersant 5468) was also prepared in an amount such that the solids ratio per weight of the bismuth ruthenium composite oxide powder that underwent the acid treatment process was 1 wt%. The ion-exchanged water and dispersant prepared as described above were then added to a predetermined amount of bismuth ruthenium composite oxide powder, and the mixture was mixed to produce a catalyst dispersion. The resulting catalyst dispersion was then pumped at a flow rate of 200 mL / min into the crushing chamber of a wet bead mill (manufactured by Ashizawa Finetech Co., Ltd., Labostar Mini DMS65) through the crushing chamber inlet. Partially stabilized zirconia (PSZ) beads with a diameter of 0.1 mm were previously placed in the crushing chamber. The stirring mechanism in the crushing chamber was then driven at a peripheral speed of 8 m / s, and the lumps of bismuth ruthenium composite oxide particles were subjected to a crushing treatment for 9 minutes. After the first stage of crushing treatment was performed in this manner, the catalyst dispersion discharged from the outlet of the crushing chamber was again introduced into the crushing chamber through the inlet of the crushing chamber, and a second stage of crushing treatment was performed. This procedure of introducing the catalyst dispersion, crushing treatment, and discharging was considered one pass, and this one pass was repeated a total of five times (5 passes). Thereafter, the catalyst dispersion was concentrated by being held in an atmosphere of 60°C for 12 hours. The solids ratio of the catalyst dispersion after concentration was 27 wt%.

[0066] (2) Manufacturing of the air electrode 1) Metal foam preparation process The air electrode core was made of sheet-shaped nickel foam 9a (thickness: 1.8 mm, average pore size: 600 μm, weight: 300 g / m 2 ) was prepared. Then, the sheet of nickel foam 9a was rolled to adjust the thickness to 0.5 mm.

[0067] 2) Gas diffusion layer precursor preparation process 50 parts by weight of high-purity natural graphite powder (SNO-1T manufactured by SEC Carbon Co., Ltd., average particle size 5 μm), 30 parts by weight (solids ratio) of PTFE dispersion as a fluororesin (polytetrafluoroethylene 31-JR manufactured by Mitsui-Chemours Fluoroproducts Co., Ltd., average particle size 0.2-0.25 μm), 10 parts by weight of ethanol, and 70 parts by weight of ion-exchanged water were prepared and kneaded to form a gum, obtaining a gas diffusion layer precursor. The obtained gas diffusion layer precursor was rolled into a sheet.

[0068] 3) Catalyst layer slurry preparation process The catalyst dispersion containing the bismuth-ruthenium composite oxide powder obtained as described above (35 parts by solid weight), 30 parts by weight of high-purity natural graphite powder (SNO-1T, manufactured by SEC Carbon Co., Ltd., average particle size 1-2 μm) as a carbon material, 15 parts by weight of manganese dioxide powder (FMH, manufactured by Tosoh Corporation, average particle size (D50) 5 μm) which is an aggregate of manganese dioxide particles, 20 parts by weight of FEP dispersion (perfluoroethylene propene copolymer 120-JRB, manufactured by Mitsui-Chemours Fluoroproducts Co., Ltd., average particle size 0.2 μm) as a fluororesin (20 parts by solid weight), 10 parts by weight of ethanol, and 70 parts by weight of ion-exchanged water were prepared and charged into the stirring vessel of a planetary centrifugal mixer. The mixture was then mixed and stirred by operating the planetary centrifugal mixer to obtain a catalyst layer slurry.

[0069] 4) Crimping process The sheet-like gas diffusion layer precursor was placed on one side of the sheet-like nickel foam 9a, and the gas diffusion layer precursor and the nickel foam 9a were pressed together to pressure-bond the two together, thereby obtaining a first composite body having the gas diffusion layer precursor on one side and the nickel foam 9a on the other side.

[0070] 5) Gas diffusion layer formation heat treatment process The first composite was placed in a heat treatment furnace. The interior of this heat treatment furnace was filled with nitrogen gas, and the first composite was placed in a nitrogen gas atmosphere. The temperature inside the heat treatment furnace was then set to 340°C and maintained for 2 hours. As a result, the gas diffusion layer precursor became the gas diffusion layer 6, and a second composite was obtained in which the gas diffusion layer 6 and nickel foam 9a were combined.

[0071] 6) Catalyst layer slurry coating process The catalyst layer slurry was applied to the other surface of the second composite, i.e., the nickel foam skeleton and the exposed portion of the gas diffusion layer between the nickel foam skeletons, using a bar coater with a wire diameter of 50 μm, thereby obtaining an intermediate air electrode product in which the catalyst layer slurry and the second composite were combined.

[0072] 7) Catalyst layer formation heat treatment process Next, the obtained intermediate product was dried at 60°C for 12 hours and then inserted into a heat treatment furnace. The interior of this heat treatment furnace was filled with nitrogen gas, and the intermediate product was placed under a nitrogen gas atmosphere. The temperature inside the heat treatment furnace was then increased to 340°C and maintained for 2 hours, thereby converting the catalyst layer slurry into a catalyst layer 8. In this manner, an air electrode 2 was obtained (see FIG. 2), which included nickel foam 9a, a gas diffusion layer 6 positioned on one side of the nickel foam 9a, and a catalyst layer 8 positioned on the other side of the nickel foam 9a. Here, FIG. 2 is a schematic cross-sectional view of the air electrode, and for the nickel foam 9a, the cross section of the skeleton of the nickel foam is shown as a circle.

[0073] The resulting air electrode 2 was a square measuring 40 mm in length and 40 mm in width and had a thickness of 200 μm. The catalyst amount of the air electrode 2 in Example 1 was 1.87 mg / cm 2 Two air electrodes 2 were prepared, one for analysis and the other for battery assembly.

[0074] (3) Battery assembly An acrylic box-shaped working electrode container 10 with a sidewall opening 20 in part of its sidewall 18 and an air electrode 2 for battery assembly were prepared. The sidewall opening 20 was rectangular, measuring 35 mm in length and 35 mm in width. The air electrode 2 was then placed over and tightly attached to the sidewall opening 20. The air electrode 2 was disposed so that the catalyst layer 8 side faced the inside of the working electrode container 10 and the gas diffusion layer 6 side faced the outside of the working electrode container 10, thereby closing the sidewall opening 20. The periphery of the air electrode 2 was then fixed to the outside of the working electrode container 10 by an acrylic frame member 22. The frame member 22 had an opening 24 in its center that was the same shape as the sidewall opening 20, and was fixed to the sidewall 18 of the working electrode container 10 with screws 26. In addition, a gasket (not shown) is provided in the area where the side wall 18 of the working electrode container 10 and the air electrode 2 overlap, and the catalyst layer 8 of the air electrode 2 is in close contact with the side wall 18 around the side wall opening 20, ensuring airtightness.

[0075] Furthermore, inside the working electrode container 10, a counter electrode 30 made of a nickel plate and having a rectangular shape of 100 mm in length and 100 mm in width was disposed at a position facing the air electrode 2.

[0076] Thereafter, a predetermined amount of alkaline electrolyte 28 was poured into the working electrode container 10. A 5 mol / L KOH aqueous solution was used as the alkaline electrolyte 28. The counter electrode 30 was completely immersed in the alkaline electrolyte 28. Furthermore, the catalyst layer 8 of the air electrode 2 was exposed to the inside of the working electrode container 10, and therefore the catalyst layer 8 of the air electrode 2 was in contact with the alkaline electrolyte 28. Meanwhile, the gas diffusion layer 6 side of the air electrode 2 was exposed to the atmosphere.

[0077] An air electrode lead 32 was electrically connected to the air electrode 2, and a counter electrode lead 34 was electrically connected to the counter electrode 30, respectively.

[0078] Next, an acrylic box-shaped reference electrode container 14 was prepared. The reference electrode container 14 had an opening 36 at the top, and a predetermined amount of alkaline electrolyte 28 was poured into the reference electrode container 14 through this opening 36. A 5 mol / L KOH aqueous solution was used as the alkaline electrolyte 28. The opening 36 was closed with a lid 38. A reference electrode 16 was disposed at a predetermined position on the lid 38. The reference electrode 16 was an Hg / HgO electrode, and approximately half of it was immersed in the alkaline electrolyte 28. The reference electrode container 14 was connected to the working electrode container 10 via a liquid junction 12 to eliminate the influence of the liquid junction potential difference. A reference electrode lead 40 was electrically connected to the reference electrode 16. In this manner, the battery 4 shown in FIG. 1 was manufactured.

[0079] (Comparative Example 1) An air electrode and a battery were manufactured in the same manner as in Example 1, except that in the catalyst layer slurry application step, the catalyst layer slurry was applied to one side of the second composite, i.e., the portion of only the gas diffusion layer 6 where the nickel foam 9a was not exposed, using a bar coater with a wire diameter of 50 μm, to obtain an intermediate air electrode product in which the catalyst layer slurry and the second composite were combined.

[0080] 3, the air electrode 2 of Comparative Example 1 has a catalyst layer 8 formed on the side opposite to the nickel foam 9a. The side on which the nickel foam 9a is located faces the outside of the battery 4, and the side on which the catalyst layer 8 is located faces the inside of the battery 4 and is in contact with the alkaline electrolyte.

[0081] The thickness of the air electrode 2 in Comparative Example 1 was 200 μm. The catalyst amount in the air electrode 2 in Comparative Example 1 was 1.14 mg / cm 2 It was.

[0082] (Comparative Example 2) The catalyst layer slurry prepared in the catalyst layer slurry preparation step was replaced with nickel foam 9a (thickness: 1.6 mm, average pore size: 600 μm, basis weight: 575 g / m). 2An air electrode and a battery were manufactured in the same manner as in Example 1, except that the catalyst layer slurry was filled into a container, the catalyst layer slurry was dried, and then rolled to adjust the thickness, and then a heat treatment similar to that in the catalyst layer formation heat treatment step was performed.

[0083] As shown schematically in Fig. 4, the air electrode 2 of Comparative Example 2 has a structure in which a catalyst mixture 80 containing graphite, manganese dioxide, and a fluororesin (FEP) is filled between the skeletons of nickel foam 9a. In other words, it is a conventional type of air electrode in which the catalyst layer and gas diffusion layer are not separated. The air electrode of Comparative Example 2 has no front or back; one side is simply positioned to face the outside of the battery 4 and open to the atmosphere, and the other side is positioned to face the inside of the battery 4 and be in contact with the alkaline electrolyte.

[0084] The thickness of the air electrode 2 in Comparative Example 2 was 200 μm. The catalyst amount in the air electrode 2 in Comparative Example 2 was 6.0 mg / cm 2 It was.

[0085] 2. Evaluation of air electrodes and air secondary batteries (1) SEM / EDS analysis of the air electrode 1) Analysis method The analytical air electrode of Example 1 was observed with a scanning electron microscope (SEM) and subjected to elemental analysis by energy dispersive X-ray spectroscopy (EDS), a so-called SEM / EDS analysis. A photograph of an SEM / EDS image (magnification: 200x, acceleration voltage: 15 kV) of the analysis results of Example 1 is shown in Figure 5. In Figure 5, the SEM image of the air electrode is shown in the center, and the distribution states of fluorine (F), nickel (Ni), and ruthenium (Ru) as the EDS analysis results corresponding to the central SEM image are shown on the right.

[0086] 2) Results and Discussion Figure 5 shows that fluorine (F) atoms originate from PTFE and are present in greater amounts in the gas diffusion layer than in the catalyst layer. Nickel (Ni) corresponds to the position of the nickel foam core. Ruthenium (Ru) originates from bismuth-ruthenium composite oxide and is present in the catalyst layer. As shown in Figure 5, the gas diffusion layer and nickel foam are pressed together, causing the gas diffusion layer to collapse and sag, complicating the interface and increasing the surface area. The catalyst layer is coated on the nickel foam and gas diffusion layer to a thickness of 10 μm to 30 μm. In this way, rather than incorporating the catalyst into the entire air electrode, the amount of catalyst used can be reduced by applying a thin layer of catalyst to the other side of the gas diffusion layer where the nickel foam core is exposed.

[0087] The three-phase interface necessary for the battery reaction is generated only in a limited area within the air electrode. That is, it is generated in the area where the catalyst (solid phase), oxygen (gas phase), and electrolyte (liquid phase) are all present. However, in a conventional air electrode such as Comparative Example 2, the catalyst is contained throughout the entire air electrode, so that the catalyst present in areas away from the electrolyte, for example, does not contribute to the battery reaction. In other words, in conventional air electrodes, a large amount of wasted catalyst is present. In the air electrode of this embodiment, focusing on this point, the catalyst is not present in the gas diffusion layer, but rather the catalyst layer is provided so that the catalyst is concentrated on the side in contact with the electrolyte. This eliminates wasted catalyst and reduces the amount of catalyst compared to conventional methods, contributing to reduced manufacturing costs of the air electrode.

[0088] The thickness required for a conventional catalyst layer varies depending on the type of catalyst, the mixing ratio, the type of electrolyte, etc., but is generally 100 μm or less. On the other hand, when a highly concentrated alkaline aqueous solution such as that used in this example is used as the electrolyte, the gas solubility is significantly reduced, resulting in a shorter diffusion distance of oxygen in the electrolyte. As a result, oxygen does not diffuse deep into the thick catalyst layer, particularly in the high-output range, and the proportion of catalyst that does not contribute to the reaction increases. After extensive research, the inventors have found that the thickness of the catalyst layer is preferably 50 μm or less, and most preferably 30 μm or less. Furthermore, in the constituent materials of the air electrode of this embodiment, the bismuth ruthenium composite oxide catalyst is used in an amount of 0.5 mg / cm per area of ​​the air electrode, depending on the required discharge characteristics. 2 ~2.0mg / cm 2 It is preferable to set the following.

[0089] (2) Electrochemical measurements 1)Measurement method Electrochemical measurements were performed by cyclic voltammetry using the air secondary batteries of Example 1 and Comparative Examples 1 and 2. First, to evaluate the output characteristics of the discharge reaction (oxygen reduction reaction), a sweep potential was set to -0.5 to 0.1 V at a sweep rate of 5 mV / sec, and the potential was returned to 0.1 V at a specified power or current of 1 A. This evaluation was performed twice. Next, to evaluate the output characteristics of the charge reaction (oxygen evolution reaction), a sweep potential was set to 0.1 to 0.65 V at a sweep rate of 5 mV / sec, and the potential was returned to 0.1 V at a specified power or current of 1 A. This evaluation was performed twice. The durability of the air electrode was evaluated by alternately repeating cyclic voltammetry in the two potential ranges described above.

[0090] The results of cyclic voltammograms for the oxygen reduction reaction described above are shown in Figures 6 and 7. In Figure 6, the horizontal axis represents the potential of the air electrode relative to the Hg / HgO reference electrode, and the vertical axis represents the value of the current flowing through the air electrode at that time. In Figure 7, the horizontal axis represents the potential of the air electrode relative to the Hg / HgO reference electrode, and the vertical axis represents the value of the current flowing through the air electrode when converted per amount of catalyst used.

[0091] 2) Results and Discussion From Figure 6, it can be seen that when the potential of the air electrode relative to the Hg / HgO reference electrode is 0.0 V or less, a current due to the oxygen reduction reaction flows. The current values ​​are negative, which is due to the reduction reaction. In Figure 6, the electrode through which a higher current flows at a higher potential (lower overvoltage) indicates a more efficient reduction reaction and superior output characteristics. It can be seen that the air electrode of Example 1 is particularly superior in high-power applications.

[0092] Furthermore, in FIG. 7, in which the vertical axis is converted to the amount of catalyst used, it can be seen that Example 1 has the most excellent output characteristics.

[0093] Here, the results of Figures 6 and 7 will be considered separately for the low output range up to 200 mA and the high output range above 200 mA.

[0094] First, because the same catalyst was used, the rise of the oxygen reduction current occurred at the same potential. This indicates the limiting current for catalytic activity. In the low-power range up to 200 mA, the catalytic reaction is rate-limiting, and the characteristics are determined by the number of active sites for the discharge reaction (the three-phase interface where the catalyst effectively works) on the air electrode. Therefore, reducing the amount of catalyst tends to decrease the characteristics (the slope decreases). However, converting this to current per amount of catalyst indicates how effectively the catalyst is being used. It can be seen that Example 1 exhibits higher output characteristics per amount of catalyst than Comparative Examples 1 and 2. This indicates that a larger portion of the catalyst contained in the air electrode is concentrated at the three-phase interface. This is thought to be due to the increased surface area caused by the complex interface between the gas diffusion layer and the catalyst layer, as shown in Figure 5.

[0095] Next, in the high-power region, the transport of materials to the reaction site is rate-limiting, and the performance is determined by the ease with which air passes through the three-phase interface. It can be seen that Example 1 is superior to Comparative Example 2, even in the high-power region. This is thought to be because, in Example 1, air is supplied to the entire catalyst layer through the gas diffusion layer, which has a high water-repellent property and many large macropores that do not allow the electrolyte to penetrate.

[0096] Furthermore, Example 1 also exhibits excellent durability against repeated charge and discharge. In Comparative Example 1, the output characteristics gradually deteriorated when cyclic voltammetry of the charge reaction (oxygen evolution reaction) and the discharge reaction (oxygen reduction reaction) was alternately repeated. After evaluation, the catalytic layer of the air electrode of Comparative Example 1 partially floated from the gas diffusion layer. This is thought to be due to poor adhesion to the gas diffusion layer. However, in Example 1, neither a deterioration in characteristics nor floating of the catalytic layer was observed. This is thought to be due to the fact that the complex bond between the gas diffusion layer and the catalytic layer, formed via the nickel foam, exerts an anchoring effect, preventing detachment.

[0097] As described above, the air electrode of Example 1 has a nickel foam core interposed between the gas diffusion layer and the catalyst layer, which creates a complex bond between the gas diffusion layer and the catalyst layer. As a result, the anchor effect prevents the catalyst layer from falling off, resulting in excellent durability. Furthermore, the complex bond described above increases the number of three-phase interfaces in the catalyst layer, thereby improving the efficiency of the discharge reaction. Furthermore, the air electrode of Example 1 has a gas diffusion layer, which ensures a diffusion path for oxygen gas to the catalyst layer, allowing oxygen to be quickly supplied to the three-phase interface of the catalyst layer. As a result, the efficiency of the discharge reaction is improved. Thus, the air electrode of Example 1 has high discharge reaction efficiency, allowing the catalyst to be concentrated in areas where three-phase interfaces are formed and reducing the amount of catalyst in areas where three-phase interfaces are difficult to form. Therefore, the air electrode of Example 1 can reduce the amount of catalyst used compared to the air electrodes of Comparative Examples 1 and 2, and also has excellent output characteristics and durability. [Explanation of symbols]

[0098] 2. Air electrode 4. Battery (secondary air battery) 6 Gas diffusion layer 8 Catalyst layer 9 Core body 9a Nickel Foam 10 Working electrode container 12 Liquid junction 14 Reference electrode container 16 Reference pole 28 Alkaline electrolyte 30 Opposite

Claims

1. An air electrode for an air secondary battery used in the positive electrode of the air secondary battery, comprising: a metal foam serving as the core of the positive electrode; a gas diffusion layer crimped to one side of the metal foam; a catalyst layer formed on the other side of the metal foam, and the gas diffusion layer is positioned at a position facing the atmosphere in the air secondary battery and includes a first conductive material having conductivity and a first fluororesin having water repellency; the catalyst layer is positioned inside the air secondary battery and includes a catalyst having a dual function of oxygen generation and oxygen reduction, a second conductive material having conductivity, and a second fluororesin having water repellency. An air electrode for an air secondary battery.

2. The air electrode for an air secondary battery according to claim 1, wherein the ratio of the first fluororesin contained in the gas diffusion layer is higher than the ratio of the second fluororesin contained in the catalyst layer.

3. The first conductive material is first graphite particles, and the second conductive material is second graphite particles, The air electrode for an air secondary battery according to claim 1, wherein the average particle diameter of the first graphite particles is larger than the average particle diameter of the second graphite particles.

4. The catalyst has a pyrochlore-type bismuth ruthenium composite oxide represented by the composition formula Bi 2 Ru 2 O 7 The air electrode for an air secondary battery according to any one of claims 1 to 3, which contains the above.

5. The air electrode for an air secondary battery according to claim 4, wherein the catalyst layer further contains manganese oxide.

6. A metal foam preparation step of preparing a metal foam; A gas diffusion layer precursor production step of producing a gum-like gas diffusion layer precursor used to form a gas diffusion layer on one side of the metal foam; A catalyst layer slurry preparation step of preparing a catalyst layer slurry used to form a catalyst layer positioned on the opposite side of the metal foam with the gas diffusion layer interposed therebetween; A crimping step of crimping the gum-like gas diffusion layer precursor produced in the gas diffusion layer precursor production step to one side of the metal foam; A gas diffusion layer formation heat treatment step of performing heat treatment on the gas diffusion layer precursor crimped to the metal foam to form the gas diffusion layer; A catalyst layer slurry coating step of coating the catalyst layer slurry on the other side of the metal foam opposite to the side where the gas diffusion layer is crimped; A method for manufacturing an air electrode for an air secondary battery, comprising a catalyst layer formation heat treatment step of performing heat treatment on the catalyst layer slurry coated on the metal foam to form the catalyst layer.

Citation Information

Patent Citations

  • Air electrode and air secondary battery using this air electrode

    JP2006196329A

  • Gas diffusion layer used for gas diffusion electrode of metal-air battery or fuel cell, gas diffusion electrode using the same, and manufacturing method thereof

    JP2020013662A

  • Air electrode for air secondary battery and air secondary battery

    JP2020077469A

Cited By

  • Bamboo charcoal integrated electrode and preparation method and application thereof

    CN121215776A